Acid-Induced Surface Functionalization of Polyoxometalate by Enclosure in a Polyhedral Silver−Alkynyl Cage - Gao, Guang-Gang; Cheng, Ping-Shing; Mak, Thomas C. W (Journal of the American Chemical Society, 2009)
Surface functionalization of polyoxometalate anions with silver(I) tert-butylethynide in an organic solution medium has been achieved for the first time using an acid-induced facile approach. The generated neutral hybrid monomeric complexes [Ag40(CC t Bu)22(CF3COO)12(V10O28)]·4CH3OH (1) and [Ag40(CC t Bu)20(CF3COO)12(Mo6O22)]·2CH3OH (2) constitute members of a new silver(I)−polyoxometalate family in which the polyoxometalate anion is embedded in a polyhedral silver(I) cluster assembled by multiple argentophilic Ag···Ag interactions.